A glucosyl triblock copolymer: synthesis and its injectable thermo- and pH-responsive behaviours. Issue 31 (8th April 2015) - Sun, Tongming; Zhu, Jinli; Wang, Miao; Lu, Minlei; Ding, Jinjin; Lv, Ziting; Hua, Ping; Zhang, Yuejun
<x xml:space="preserve">Abstract</x> A new glucosyl triblock PGNA copolymer was first synthesized and the aqueous PGNA copolymer solution exhibits good sol–gel phase transition behaviours. The formed hydrogels are sensitive to the temperature and pH.